Church mother: the writings of a Protestant reformer in sixteenth-century Germany - Zell, Katharina (The other voice in early modern Europe, 2006)
Letter to the suffering women of the community in Kentzingen -- Katharina Schütz's apologia for Master Matthew Zell, her husband -- Some Christian and comforting songs of praise about Jesus Christ our Savior -- Lament and exhortation of Katharina Zell to the people at the grave of Master Matthew Zell -- The Miserere Psalm meditated, prayed, and paraphrased with King David by Katharina Zell--, sent to the Christian man Sir Felix Armbruster -- To Caspar Schwenckfeld -- A letter to the whole citizenship of the city of Strasbourg from Katharina Zell,--concerning Mr. Ludwig Rabus -- Letter of Ludwig Rabus to Katharina Schütz Zell